Diagnostic value of pleural fluid adenosine deaminase level in patients of tubercular pleural effusion - Goyal, Amit; Kaur, Amanpreet; Kajal, N. C. (International Journal of Advances in Medicine, 2020)
Background: The diagnosis of tuberculosis (TB) continues to be a challenge in clinical practice. Traditional diagnostic methods are very useful but don't provide enough sensitivity and specificity. Adenosine deaminase (ADA) has been developed and widely used for the diagnosis of TB. This article reviews the characteristics, metabolism and clinical uses of ADA for the diagnosis of TB in clinical practices. Methods: This study was carried out in the department of chest and TB, GMC, Amritsar, Punjab, India. In this study total 50 who attended outpatient department (OPD) and indoor patients of adult age and either sex were taken. Patients with pleural effusion as determined by clinical and or radiological means, thoracocentesis on who yield a minimum amount of fluid enough to carry out routine test were included in the study. Results: Most of the patients were between the age group of 15-34 years, of those 72% were males and 28% female. Most of the patients of tuberculous effusion were from younger age group between 25-34 years. Most common symptom was breathlessness (90%) followed by fever (75%), cough (75%) then chest pain (72%). The diagnosis of TB was made in 40 patients (80%), while in 10 patients (20%) TB were excluded (malignancy and miscellaneous disease) based on history, clinical and laboratory findings. Sensitivity of ADA in diagnosing TB pleural effusion was 95% and specificity 80%. Conclusions: ADA level of the pleural fluid is a non-invasive test. Pleural fluid ADA is useful in early diagnosing of tuberculosis pleural effusion. So the analysis of ADA levels can be done simply, quickly and cheaply.